2010
DOI: 10.1016/j.foodchem.2010.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate enhances iron uptake into intestinal cells through formation of a FeCl3–ascorbate complex

Abstract: Abstract:It has been well documented that ascorbate enhances iron uptake with a proposed mechanism based on reduction to the more absorbable ferrous form. We have performed a study on the effects of ascorbate on ferric iron uptake in the human epithelial Caco-2 cell-line. Ascorbate increased uptake in a concentration-dependent manner with a significant difference between iron uptake and reduction. Uptake kinetics are characteristic of a non-essential activator and the formation of a Fe 3+ -ascorbate complex. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…However, this complex cannot be compared in efficiency with other chelating molecules responsible for iron transport, primarily DMT1 (divalent metal transporter 1) [81]. In addition to its wellestablished reduction of ferric iron to provide a bioavailable supply of ferrous iron to DMT1, ascorbic acid also directly enhances directly the uptake of ferric iron into Caco-2 cells through the formation of the Fe 3+ -ascorbate complex [82]. Since DMT1 is not involved in the uptake of this complex, further work is required to identify the transporter system (chelating agent) which inhibits Fe 3+ reduction by ascorbate.…”
Section: Discussionmentioning
confidence: 99%
“…However, this complex cannot be compared in efficiency with other chelating molecules responsible for iron transport, primarily DMT1 (divalent metal transporter 1) [81]. In addition to its wellestablished reduction of ferric iron to provide a bioavailable supply of ferrous iron to DMT1, ascorbic acid also directly enhances directly the uptake of ferric iron into Caco-2 cells through the formation of the Fe 3+ -ascorbate complex [82]. Since DMT1 is not involved in the uptake of this complex, further work is required to identify the transporter system (chelating agent) which inhibits Fe 3+ reduction by ascorbate.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was suggested that there are several routes of iron accumulation in cells, including the ascorbate-dependent ferrous iron uptake via the divalent metal transporter (DMT1), plus an independent route for ferric iron uptake [ 39 , 99 ]. For example, it was previously demonstrated that the reduction of ferric iron by ascorbic acid provides bioavailable ferrous iron to DMT1, and also directly enhances the uptake of ferric iron into Caco-2 cells through the formation of an Fe 3+ –ascorbate complex [ 109 ]. The Caco-2 cell line consists of human epithelial colorectal adenocarcinoma cells, which are generally used as an in vitro model of the human small intestinal mucosa to predict the absorption of orally administered drugs [ 109 ].…”
Section: Biological Implications Of the Iron Complexes Of Ascorbicmentioning
confidence: 99%
“…Beans are also an important source of non-digestible carbohydrates which may impair iron absorption (Luo, Xie, & Cui, 2010. However, controversies remain as some of these foods, such as cabbage (kale) are also good sources of ascorbic acid which improves iron absorption (Thumser, Rashed, Sharp, & Lodge, 2010).…”
Section: Meat a Valuable Iron Sourcementioning
confidence: 99%